Neuroscience in gambling policy and treatment: an interdisciplinary perspective. (June 2017) - Yücel, Murat; Carter, Adrian; Allen, Amy R; Balleine, Bernard; Clark, Luke; Dowling, Nicki A; Gainsbury, Sally M; Goudriaan, Anna E; Grant, Jon; Hayes, Alan; Hodgins, David; van Holst, Ruth; et al.
Summary: Neuroscientific explanations of gambling disorder can help people make sense of their experiences and guide the development of psychosocial interventions. However, the societal perceptions and implications of these explanations are not always clear or helpful. Two workshops in 2013 and 2014 brought together multidisciplinary researchers aiming to improve the clinical and policy-related effects of neuroscience research on gambling. The workshops revealed that neuroscience can be used to improve identification of the dangers of products used in gambling. Additionally, there was optimism associated with the diagnostic and prognostic uses of neuroscience in problem gambling and the provision of novel tools (eg, virtual reality) to assess the effectiveness of new policy interventions before their implementation. Other messages from these workshops were that neuroscientific models of decision making could provide a strong rationale for precommitment strategies and that interdisciplinary collaborations are needed to reduce the harms of gambling.